Alterations of antioxidant enzymes in preeclampsia - Krishna, Thanikonda Sharmila; Rao, Epari Venkata; Naidu, Jupalle Nagaiah (International Journal of Research in Medical Sciences, 2017)
Background: Pregnancy is a stressful condition in which many physiological and metabolic functions are altered to considerable extent and hypertension is the most common problem encountered during pregnancy, complicating 5-10% of pregnancies. Recent reports suggest that free radical induced endothelial damage as an important factor in the pathogenesis of preeclampsia. Such cell injury might in turn is counteracted by the action of several in vivo antioxidants. The aim of present study was to determine the activity of enzymatic antioxidants - glutathione peroxidase and catalase in preeclampsia. Methods: Thirty cases of preeclampsia and thirty gestational age matched normotensive pregnant women attending Narayana General Hospital, Nellore were included in the study. The antioxidant enzymes - RBC glutathione peroxidase and catalase activities were determined by the respective laboratory methods in preeclampsia cases and compared with that of normotensive pregnant women. Results: The activity of catalase was significantly decreased (mean ± SEM 5.6 ± 0.26 vs. 8.5 ± 0.32 k/ml) and that of glutathione peroxidase was significantly increased (mean ± SEM 103.9 ± 1.67 vs. 83.8 ± 1.85 U/gm of Hb) in preeclamptic cases when compared with that of normotensive pregnant women. Conclusions: We conclude that activities of antioxidant enzymes-glutathione peroxidase and catalase are altered in preeclampsia. The increased activity of the antioxidant enzymes may be a compensatory regulation in response to increased oxidative stress while the decreased activity supports that lipid peroxidation is an important causative factor in the pathogenesis of preeclampsia.